Improvement of overall equipment effectiveness through application of single-minute exchange of die in automotive manufacturing - Abdul Rasib, Amir Hamzah; Abdullah, Rohana; Ebrahim, Zuhriah; Mohamad Rafaai, Zubaidi Faiesal (The Mattingley Publishing Co., Inc, 2019)
In manufacturing, every process is performed according to the planned operation time. Wastes will be generated when downtime occurs and if correct standard operations are not followed affecting the manufacturing performance. Every company aims to eliminate waste in order to increase their performance and productivity. Therefore, this study attempts to improve the Overall Equipment Effectiveness (OEE) via the application of Single Minutes Exchange of Die (SMED) to improve the operation efficiency at an automotive industry manufacturing operation. Results of this study show improvement in the productivity and OEE rate. Thus, the application of SMED proved to improve the OEE performance measures and concurrently increase operation productivity